Prediction of Coronavirus anxiety based on the meaning in life and intimacy of family members among housewife mothers - Rakhshandeh, Ala; Doroudian, Nadereh; Nemati jahan, Nasrin; Rostamnezhad, Mehri (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study aimed to determine the role of the meaning in life and intimacy of family members in predicting Coronavirus anxiety among housewife mothers. Methods: The present study was applied and descriptive-correlational. The statistical population of the study included all housewives in Karaj city in 2020. The convenience sampling method was used to select 192 people from the population. The data were collected using the Alipour et al.’s Corona Anxiety Scale (2015), the meaning in life questionnaire of Steger, Frazier, Oishi, and Caller (2006), Walker and Thompson (1983) intimacy scale. The simultaneous multiple regression method was used to determine the role of each variable in predicting Coronavirus anxiety. Results: The results of the present study indicated that there is a significant negative relationship between Coronavirus anxiety and the meaning in life and family intimacy. The variable of meaning in life and family intimacy can significantly predict Coronavirus anxiety among housewives. The variables of meaning in life and family intimacy have explained 35.5% of the variance of Coronavirus anxiety among women. The analysis of regression coefficients indicated that the meaning in life variable (p <0.01, β = 0.426) and family intimacy (p <0.01, β = -0.348) negatively and at a significant level of 0.01 predict Coronavirus anxiety among housewives. Conclusion: The findings of this study nicely determined that the unique role of meaning in life has a greater role in predicting Coronavirus anxiety than family intimacy.